Penelitian Tentang Waralaba (Franchise) Apakah Merupakan Salah Satu Bentuk Perjanjian Tertentu Yang Diatur Dalam KUH perdata - Khumarga, Dahnial (LAW REVIEW, 2002)
Franchise agreement is generally an agreement between a supplier of a product or Â service or an owner of a desired trademark or copyright (FRANCHISOR), and a reseller (FRANCHISEE) under which the franchisee agrees to sell the franchisors product or service or to do business under the franchisors name. A franchise is an agreement which gives the transferee the right to distribute, sell or provide goods, services or facilities, within a specified area, the cost of obtaining a franchise may be amortized over the life of the agreement. In agreement, a franchise is a capital asset and results in capital gains, or loss if all significant powers, rights on continuing interests are transferred pursuant to the sale of a franchiseÂ